ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA KELAS X SMA NEGERI 2 GRABAG - Rochayanah, Siti; Warniasih, Kristina (Jurnal Citra Pendidikan, 2024)
The aim of this research is to describe the critical thinking abilities of class X SMA Negeri 2 Grabag students. The research method used was qualitative with a research focus on the subject of three class X-2 students at SMA Negeri 2 Grabag, who represented various levels of ability, namely high group students, medium group students and low group students. Data collected through a written test which includes critical thinking indicators in mathematics interviews. The research results showed that there were 23% of students in the high category, 63% of students in the medium category, and 14% of students in the low category. Students in the high group are able to master all indicators of critical thinking in statistics material. Students with moderate abilities show good abilities except for some deficiencies in interpretation and analysis. Students with low abilities tend to have limitations in data interpretation, inference and other critical thinking skills such as analysis, evaluation and inference. The implication of these findings is the need for learning strategies to improve students' critical thinking skills in understanding and applying statistical concepts.